Texas Shoot-out, avagy biztosítéki konstrukciók a szindikátusi kötelemben - Szabó, Gergely (Debreceni Jogi Műhely, 2012)
The shareholders agreement is considered a typical contract. This agreement is concluded by and between the members of the company in order to establish the rules of the cooperation among them, their behaviour towards and expectations from each other in connection with the company. The agreement is often used in the practice, since its flexible construction enables to rule various types of transaction. For example, in Hungary there is a growing tendency i.e.the major investments and joint venture agreements are being established in the frame of a shareholders’ agreement. On the other hand, drafting such a contract is a complex procedure. This type of agreement is not governed by specific law, therefore the general rules of the contract law may be linefore. Furthermore the shareholders’ agreement is located at the borderline between the civil and company law, and in a given case it might be complicated to enforce the provisions of the agreement. For example, if the member breaches the voting provision outlined in the shareholders’ agreement, then the resolution passed upon the contract breach cannot be challenged. Due to lack of a specific law, the practice created the adequate legal securities to ensure the enforcement of the cooperation structure outlined in the shareholders’ agreement. As the first analysed security, the purpose of the buy-out clauses (Russian Roulette, Texas Shoot-out, Dutch Auction, Put-Option, Call-Option) is to ensure the company’s permanent operation, if there is an insoluble dispute among the members, which obstructs the decision making, and consequently the operation of the company, as well. The concept of the buy-out clause is to settle the dispute in the way of taking over the participation of the involved member by another member. The exit clauses (Drag Along, Carry Along) aimed to encumber or to unburden the step out from the company. The entitled person is able to sell the shares of the remaining members to the buyer, or to oblige the seller to sell his own and the entitled person’s participations jointly to the buyer. The takeover clauses’ (Control Flip Over, Swiss Clause) duty is to enable the enforcement of the corporate legal obligations outlined in the agreement. If a member fails to fulfil his obligations, the entitled person may acquire his participation, which will enable him to pass the necessary resolution in the members meeting (general meeting). After the voting, the “seller” is entitled to buy back his participation at the same price. If the members want to exclude acquiring participation by third persons in the company without their approval, there are adequate securities to be specified in the shareholders’ agreement (for example the right of first refusal, option right). By the specific type of shareholders’ agreement the creditor makes investments in the company and becomes member in order to secure the transaction. If the company or the original owners of the company breach the contract, they will be held individually liable till the limit of the investmented amount. The shareholders’ agreement is an efficient option to rule major transactions, and with the help of the securities described in this study, the investor could feel his money in safe. On the other hand, there are still a lot of questions to be answered. For example the compliance of these securities with the strict provisions of the law. It is the duty of the practice to reveal the answers.